2022
DOI: 10.1039/d2lc00481j
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial chemotaxis in static gradients quantified in a biopolymer membrane-integrated microfluidic platform

Abstract: Chemotaxis is a fundamental bacterial response mechanism to changes in chemical gradients of specific molecules known as chemoattractant or chemorepellent. The advancement of biological platforms for bacterial chemotaxis research is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…They typically can be categorized as one of two types. In the first, the CG is set up solely through analyte diffusion, which has the disadvantage of often needing hours to establish a gradient that then continuously changes in time, which can complicate the interpretation of experimental results [ 43 , 44 ]. The second type uses advection to continuously supply source and sink fluids to the CG region [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…They typically can be categorized as one of two types. In the first, the CG is set up solely through analyte diffusion, which has the disadvantage of often needing hours to establish a gradient that then continuously changes in time, which can complicate the interpretation of experimental results [ 43 , 44 ]. The second type uses advection to continuously supply source and sink fluids to the CG region [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Antibiotics with strong interaction with alginate hydrogel such as tetracycline [ 48 ] were excluded. It has been previously shown that small molecules such as fluorescein, glucose, peptides, and antibiotics can freely diffuse through the alginate hydrogels [ 34 , 35 , [49] , [50] , [51] ] as the pore size of the alginate hydrogel prepared with 1% w/v should be around tens of nanometers [ 52 , 53 ]. Together, these observations suggest that the alginate hydrogel did not limit the diffusion of the selected antibiotics.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the current system has a limited experimental window of 30 min before the gradient is dissipated, which is shorter than the time frames used to study behaviour in static gradients. 55 However, static systems require continuous replenishment of source and sink, which adds complexity to the experimental setup.…”
Section: Planariansmentioning
confidence: 99%